Pengaruh Positive Parenting Terhadap Perkembangan Karakter Siswa Di SDIT Al-Ghazali Pamekasan - Imam Abu Wildan (PT. Nawa Edukasi Nusantara, 2026)
The family is the first environment that plays a fundamental role in shaping children's personality and character. Positive parenting, characterized by warmth, open communication, appreciation, and active parental involvement, is believed to foster optimal character development in children. However, the persistently high incidence of violence against children indicates that positive parenting practices have not been widely implemented. This study aimed to determine whether positive parenting influences the character development of students at SDIT Al-Ghazali Pamekasan and to examine the extent of its influence. This research employed a quantitative approach using a causal-comparative design. The population consisted of all students in Grades 3 to 6 at SDIT Al-Ghazali Pamekasan, with a sample of 47 parents selected through purposive sampling. Data were collected using Likert-scale questionnaires to measure positive parenting practices and students' character development. The data were analyzed using validity and reliability tests, normality and linearity tests, simple linear regression, and the coefficient of determination with the assistance of SPSS version 25. The findings revealed that positive parenting had a significant effect on students' character development. This was evidenced by the F-test result, which showed an F-value of 26.981 with a significance level of 0.000 (< 0.05). Therefore, the alternative hypothesis (H₁) was accepted, while the null hypothesis (H₀) was rejected. The coefficient of determination (R²) was 0.375, indicating that positive parenting accounted for 37.5% of the variance in students' character development, while the remaining 62.5% was influenced by other factors not examined in this study.